2018
DOI: 10.48550/arxiv.1807.08736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quasi-local Energy in 3D Gravity with Torsion

Cheng-Hao Wei,
Bo Ning

Abstract: We show that for generic stationary spacetime and a series of Killing fields, Wald's approach for quasi-local energy could always be generalized to the first order formalism straightforwardly without introducing the Lorentz-Lie derivative. Via this approach, we derive the general formula for the black hole entropy in the three dimensional torsional Mielke-Baekler gravity, reproducing correctly the total energy, the angular momentum as well as the black hole entropy for the BTZ-like solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is worth noting here that in Refs. [36][37][38] it is found that torsion does not contribute to black hole entropy in Riemann-Cartan spacetimes (see, however, Ref. [39]).…”
Section: Black Hole Entropymentioning
confidence: 99%
“…It is worth noting here that in Refs. [36][37][38] it is found that torsion does not contribute to black hole entropy in Riemann-Cartan spacetimes (see, however, Ref. [39]).…”
Section: Black Hole Entropymentioning
confidence: 99%
“…In summary, our analysis explains how the double Witt and bms 3 algebras arise from the current algebra. For generality we perform this study on the most general first order theory [50][51][52][53][54][55][56][57][58][59][60][61][62], which allows for the presence of curvature, torsion, and three independent central charges.…”
Section: Motivationsmentioning
confidence: 99%